The effects of additional niacin during gestation and lactation on sow and litter performance - T L Weeden; D F Li; Robert D Goodband; Jim L Nelssen (Kansas Agricultural Experiment Station Research Reports, 1990)
One hundred and twenty-one first-litter sows were utilized to evaluate the effects of additional niacin on sow and litter performance through two parities. The control diet provided sows with 50 mg/d niacin during gestation and 100 mg/d niacin during lactation. Dietary treatments were formulated to provide sows with either 5 or 10 times the level of supplemental niacin in the control diet. Litter size was equalized within dietary treatment by 24 hr after farrowing. During the first parity, total pigs born, number of pigs born alive, and pigs equalized per litter decreased then increased as dietary niacin level increased. However, sows fed additional niacin tended to wean more pigs per litter and, therefore, had greater pig survival from birth to weaning. Pig and litter weights at weaning were increased by increasing levels of additional niacin. Sows fed the intermediate level of added niacin had the greatest weight and backfat loss during lactation. During the second parity, additional niacin had no effect on the total number of pigs born or number born alive. However, the number of pigs equalized per litter increased then decreased as niacin intake increased. There were no differences in the number of pigs weaned, pig survival, pig weight, and litter weight at weaning from dietary treatment. These results suggest that first-litter sows fed the intermediate level of additional niacin during gestation and lactation had fewer total pigs born and born alive. However, these sows had more pigs at weaning, better pig survival, and heavier litters at weaning than those fed the 50/100 mg/d niacin gestation/lactation sequence. In addition, the decrease in pigs born and born alive during the first parity was not observed in the second parity.; Swine Day, Manhattan, KS, November 15, 1990
Keywords: Swine day; 1990; Kansas Agricultural Experiment Station contribution; no. 91-189-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 610; Swine; Sow; Performance; Niacin; Gestation; Lactation